Usability evaluation of newspapers-on-DVD of the Rizal Library, Ateneo de Manila University - Santos, Engracia S. (School of Library and Information Studies, University of the Philippines Diliman, 2011)
A user-centered system has always been said to be appreciated by its desired clients, simply because the users themselves are part of its development. The primary objective of this study is to determine the usability of the Newspapers-on-DVD (NP-DVD) as perceived by its users, and to make recommendations that will help improve the product and expand its usage. To determine the usability of the NP-DVD a descriptive evaluative research method through usability testing was used in this study. This method allows the representative users to evaluate the system by performing tasks that will help uncover important problems and issues affecting the usability of the system.